Proton exchange membrane and preparation method and application thereof
By coating the perfluorosulfonic acid resin layer with different EW values in the proton exchange membrane and adding a leveling process, the problem that the existing proton exchange membrane is difficult to regulate water management capabilities is solved, and effective regulation of the membrane electrode water management capabilities and improvement of battery performance is achieved.
Patent Information
- Application Number
- CN202311181479.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-14
AI Technical Summary
In existing proton exchange membrane fuel cells, it is difficult to effectively regulate water management capabilities in enhanced proton exchange membranes, resulting in difficulty in adjusting water management capabilities of membrane electrodes and large cost investment.
By coating perfluorosulfonic acid resin solutions with different EW values on both sides of the micropore reinforcement layer and adding a leveling process, a proton exchange membrane with different water retention rates is prepared, thereby achieving effective regulation of the water management capability of the membrane electrode.
The proton exchange membrane with corresponding water retention rate is realized according to the working conditions, effectively regulate the water management ability of the membrane electrode, enhance the reverse diffusion effect of the battery electrochemical reaction, provide more ion channels for the catalytic layer, and reduce the contact resistance between the catalytic layer and the proton exchange membrane.
Smart Images

Figure CN119627135A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of fuel cells, and in particular to a proton exchange membrane and a preparation method and application thereof. Background Art
[0002] The membrane electrode of a proton exchange membrane fuel cell is mainly composed of a proton exchange membrane, a catalyst layer and a diffusion layer. The proton exchange membrane is the core component of a proton exchange membrane fuel cell and plays a key role in the battery performance. The proton exchange membrane has two main functions in a fuel cell: on the one hand, it separates the anode and cathode reaction gases; on the other hand, the proton exchange membrane provides a channel for the migration and transport of protons, allowing protons to pass through the membrane from the anode to the cathode, forming a loop with the electron transfer of the external circuit, and providing current to the outside world. Therefore, the performance of the proton exchange membrane plays a very important role in the performance of the fuel cell, and its quality directly affects the service life of the battery.
[0003] At present, enhanced proton exchange membrane has become the mainstream technical solution at this stage. It is obtained by coating a perfluorosulfonic acid resin solution on both sides of a microporous enhanced membrane and drying it. The proton exchange membrane obtained by this method cannot effectively regulate the water management capacity of the proton exchange membrane. The traditional solution mainly adjusts the water management capacity of the membrane electrode by adjusting the GDL in the membrane electrode or improving the hydrophilicity and hydrophobicity of the catalyst layer. The process is complex, there are many control parameters, the water management capacity of the membrane electrode is difficult to adjust, and the cost investment is large.
[0004] CN102304234A discloses a method for preparing a dense composite proton exchange membrane, comprising the following steps: dissolving a perfluorosulfonic acid resin with a low-boiling point alcohol aqueous solution to prepare a perfluorosulfonic acid resin solution, adding a high-boiling point solvent to the solution to replace the low-boiling point solvent, and then adding a water-retaining substance; then uniformly dropping the resin solution with the water-retaining substance onto the surface of the PTFE porous substrate membrane, heating to volatilize the solvent and heat-treating to obtain a composite proton exchange membrane, and rolling to obtain a proton exchange membrane. The patent improves the water-retaining capacity of the exchange membrane by adding a resin solution with a water-retaining substance, but the components of silica, heteropolyacid, or a mixture of silica and heteropolyacid are inorganic small molecule particles, which have poor compatibility with perfluorosulfonic acid resin, and it is difficult to control their dispersion, which easily leads to uneven thickness of the perfluorosulfonic acid resin layer, which in turn leads to a decrease in the water-retaining capacity of the proton exchange membrane, and the water-retaining rate of the proton exchange membrane is consistent as a whole and cannot be regulated.
[0005] In view of this, the present invention is proposed. Summary of the invention
[0006] One of the purposes of the present invention is to provide a proton exchange membrane, the proton exchange membrane comprising a first perfluorosulfonic acid resin layer, a microporous reinforcement layer and a second perfluorosulfonic acid resin layer stacked in sequence; wherein the EW value of the first perfluorosulfonic acid resin is 600-800, and the EW value of the second perfluorosulfonic acid resin is 900-1100. The present invention obtains a proton exchange membrane with different water retention rates by coating perfluorosulfonic acid resin solutions with different EW values on both sides of the microporous reinforcement layer, thereby achieving the purpose of effectively regulating the water management capacity of the membrane electrode.
[0007] The second object of the present invention is to provide a method for preparing the proton exchange membrane, the method comprising the following steps: coating one side of the microporous reinforcement layer with a perfluorosulfonic acid resin solution of a certain EW value, and then sequentially performing first drying-leveling-second drying; coating the other side of the microporous reinforcement layer with a perfluorosulfonic acid resin solution of another EW value, and then sequentially performing first drying-leveling-second drying; performing hot pressing; and obtaining the proton exchange membrane. The preparation method adds a leveling process, which can effectively improve the surface flatness of the proton membrane, and can effectively improve the surface flatness of the proton membrane, which is beneficial to reducing the contact resistance between the proton membrane and the catalyst layer.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] In a first aspect, the present invention provides a proton exchange membrane, the proton exchange membrane comprising a first perfluorosulfonic acid resin layer, a microporous reinforcement layer, and a second perfluorosulfonic acid resin layer stacked in sequence;
[0010] Among them, the EW value of the first perfluorosulfonic acid resin is 600-800, for example, it can be 600, 620, 640, 660, 680, 700, 720, 740, 760, 780, 900, etc., and the EW value of the second perfluorosulfonic acid resin is 900-1100, for example, it can be 900, 920, 940, 960, 980, 1000, 1020, 1040, 1060, 1080, 1100, etc.
[0011] In the present invention, a proton exchange membrane is obtained by coating perfluorosulfonic acid resin solutions in different EW value ranges on both sides of a microporous reinforcement layer. The proton exchange membrane obtained by this method can selectively select a proton exchange membrane with a corresponding water retention rate according to the use conditions, effectively regulate the water management capacity of the membrane electrode, and prepare a proton exchange membrane with different water retention rate differences on both sides, thereby enhancing the back diffusion effect of water generated by the electrochemical reaction of the battery, providing more ion channels for the catalyst layer to enable it to have a rapid activation function, and at the same time maintaining the water content in the proton exchange membrane and the catalyst layer during dry operation, effectively avoiding the high resistance problem under low humidity conditions.
[0012] Preferably, the thickness of the first perfluorosulfonic acid resin layer is 1-20 μm, for example, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc.
[0013] Preferably, the thickness of the second perfluorosulfonic acid resin layer is 1-20 μm, for example, 1 μm, 2 μm, 4 μm, 6 μm, 8 μm, 10 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, etc.
[0014] Preferably, the microporous reinforcement layer is a porous polytetrafluoroethylene (e-PTFE) film layer.
[0015] Preferably, the thickness of the porous polytetrafluoroethylene film layer is 3-100 μm, for example, 3 μm, 4 μm, 6 μm, 8 μm, 10 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, etc.
[0016] Preferably, the pore size of the porous polytetrafluoroethylene film layer is 0.05-1.0 μm, for example, it can be 0.05 μm, 0.06 μm, 0.08 μm, 0.1 μm, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, etc.
[0017] Preferably, the porosity of the porous polytetrafluoroethylene film layer is 40-90%, for example, it may be 40%, 50%, 60%, 70%, 80%, 90%, etc.
[0018] In a second aspect, the present invention provides a method for preparing a proton exchange membrane as described in the first aspect, wherein the preparation method comprises the following steps:
[0019] After coating one side of the microporous reinforcement layer with a perfluorosulfonic acid resin solution with an EW value, first drying-leveling-second drying is performed in sequence; then coating the other side of the microporous reinforcement layer with a perfluorosulfonic acid resin solution with another EW value, first drying-leveling-second drying is performed in sequence; hot pressing is performed; and the proton exchange membrane is obtained.
[0020] In the present invention, a proton exchange membrane with different water retention rates is obtained by coating perfluorosulfonic acid resin solutions with different EW values on both sides of a PTFE microporous layer, and a leveling process is added at the same time, and an alcohol-water mixture is sprayed on the surface of the depolymerized resin layer to level and dry the resin layer, which can effectively improve the surface flatness of the proton membrane and is beneficial to reducing the contact resistance between the proton membrane and the catalyst layer.
[0021] Preferably, the solid content of the perfluorosulfonic acid resin solution is 5-50%, for example, it can be 5%, 6%, 8%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.
[0022] Preferably, the temperatures of the first drying and the second drying are independently 50-70°C, for example, 50°C, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, etc.
[0023] Preferably, the first drying time is 10-120 min, for example, it can be 10 min, 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, etc.
[0024] Preferably, the first drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 wt %, for example, 5 wt %, 4 wt %, 3 wt %, 2 wt %, 1 wt %, etc.
[0025] Preferably, the second drying time is 10-120 min, for example, it can be 10 min, 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, etc.
[0026] Preferably, the second drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 wt %, for example, 5 wt %, 4 wt %, 3 wt %, 2 wt %, 1 wt %, etc.
[0027] Preferably, the leveling method comprises the following steps: spraying an alcohol-water mixture onto the surface of the perfluorosulfonic acid resin layer formed after the first drying.
[0028] Preferably, the volume ratio of alcohol to water in the alcohol-water mixture is (0.5-1):1, for example, it can be 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, etc.
[0029] Preferably, the alcohol in the alcohol-water mixture is selected from C1-C5 (for example, it can be C1, C2, C3, C4, C5) straight-chain or branched alkyl alcohol, for example, it can be methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, etc., preferably ethanol and / or n-propanol, and more preferably ethanol.
[0030] Preferably, the spraying density is 1-10 μL / cm 2 , for example, 1 μL / cm 2 , 2μL / cm 2 , 3μL / cm 2 , 4μL / cm2 , 5μL / cm 2 , 6μL / cm 2 , 7μL / cm 2 , 8μL / cm 2 , 9μL / cm 2 , 10μL / cm 2 wait.
[0031] Preferably, the temperature of the hot pressing is 80-200°C, for example, it can be 80°C, 90°C, 100°C, 110°C, 120°C, 130°C, 140°C, 150°C, 160°C, 170°C, 180°C, 190°C, 200°C, etc.
[0032] As a preferred technical solution of the present invention, the method for preparing the proton exchange membrane comprises the following steps:
[0033] S1 Preparation of the first perfluorosulfonic acid resin layer: After coating a first perfluorosulfonic acid resin solution with an EW value of 600-800 on one side of the porous polytetrafluoroethylene film, drying is performed for the first time, and then a mixed solution of alcohol and water with a volume ratio of (0.5-1):1 is sprayed on the surface of the first perfluorosulfonic acid resin layer for leveling, and drying is performed for the second time;
[0034] S2 Preparation of the second perfluorosulfonic acid resin layer: After coating the second perfluorosulfonic acid resin solution with an EW value of 900-1100 on the other side of the porous polytetrafluoroethylene film, drying is performed for the first time, and then the surface of the first perfluorosulfonic acid resin layer is sprayed with an alcohol-water mixture with a volume ratio of alcohol to water of (0.5-1):1 for leveling, and drying is performed for the second time;
[0035] S3 hot pressing: hot pressing the composite membrane obtained in S2 at 80-200° C. and a pressure of 1-10 MPa to obtain the proton exchange membrane.
[0036] In a third aspect, the present invention provides a use of the proton exchange membrane as described in the first aspect in the preparation of a fuel cell.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] (1) The present invention prepares proton exchange membranes with different water retention rates, and the proton exchange membrane with the corresponding water retention rate can be selected according to the use conditions, so as to effectively regulate the water management capacity of the membrane electrode;
[0039] (2) The present invention adds a flattening process, which can effectively improve the surface flatness of the proton membrane and help reduce the contact resistance between the proton membrane and the catalyst layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0040] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0041] Figure 1 It is a schematic diagram of the structure of the proton exchange membrane of the present invention.
[0042] Wherein, 1 is the first perfluorosulfonic acid resin layer, 2 is the microporous reinforcement layer, and 3 is the second perfluorosulfonic acid resin layer. DETAILED DESCRIPTION
[0043] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.
[0044] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.
[0045] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0046] It should be noted that similar reference numerals and letters denote similar items in the following drawings, and therefore, once an item is defined in one drawing, further definition and explanation thereof is not required in subsequent drawings.
[0047] In the description of the present invention, it should be noted that the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inside", "outside", etc. indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, or the positions or positional relationships in which the product of the invention is usually placed when in use. They are only for the convenience of describing the present invention and simplifying the description, and do not indicate or imply that the device or element referred to must have a specific position, be constructed and operated in a specific position, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.
[0048] In addition, the terms "horizontal", "vertical", "overhanging" and the like do not mean that the components are required to be absolutely horizontal or overhanging, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.
[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] The present invention is further described below by way of examples. Unless otherwise specified, the materials in the examples are prepared according to existing methods or directly purchased from the market.
[0051] Example 1
[0052] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0053] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0054] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0055] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0056] Example 2
[0057] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0058] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 800, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0059] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0060] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0061] Example 3
[0062] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0063] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0064] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 1100 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0065] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0066] Example 4
[0067] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 800, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0068] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 1100 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0069] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0070] Example 5
[0071] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0072] S1 selects a 5μm e-PTFE film (pore size of 0.1μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720 on one side, with a wet film thickness of 50μm. After drying at 60°C for 45min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and dried at 60°C for 30min until the liquid content drops below 5wt%, thereby obtaining a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side;
[0073] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 50 μm. After drying at 60° C. for 45 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0074] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0075] Example 6
[0076] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0077] S1 selects a 20 μm e-PTFE film (pore size of 1.0 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720 on one side, with a wet film thickness of 200 μm. After drying at 60° C. for 100 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0078] S2: coating the other side of the proton exchange membrane with a perfluorosulfonic acid resin solution having a solid content of 10% and an EW value of 900, with a wet film thickness of 200 μm, drying at 60° C. for 100 min until the liquid content drops below 5wt%, and then spraying an ethanol-water mixture having an alcohol-water volume ratio of 0.6:1 on the surface, drying at 60° C. for 30 min until the liquid content drops below 5wt%, to obtain a proton exchange membrane having a second perfluorosulfonic acid resin layer on the other side;
[0079] S3 puts the above sample into a hot press at a temperature of 150° C. and a pressure of 5 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0080] Example 7
[0081] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0082] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.5:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0083] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with a volume ratio of 0.5:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0084] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0085] Example 8
[0086] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0087] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 1:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0088] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with a volume ratio of 1:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0089] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0090] Example 9
[0091] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0092] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720 on one side, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, a n-propanol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0093] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then a n-propanol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0094] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0095] Example 10
[0096] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0097] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720 on one side, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, a methanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0098] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then a methanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0099] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0100] Embodiment 11
[0101] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0102] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, a glycerol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 120 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0103] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then a glycerol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 120 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0104] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0105] Example 12
[0106] This embodiment provides a proton exchange membrane, which is prepared by the following method:
[0107] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of it with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 720, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0108] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 900 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes until the liquid content drops below 5wt%, a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side is obtained;
[0109] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0110] Comparative Example 1
[0111] This comparative example provides a proton exchange membrane, which is prepared by the following method:
[0112] S1 selects a 10 μm e-PTFE film (pore size of 0.5 μm, porosity of 60%), places it on a heatable vacuum adsorption table, turns on the vacuum, and coats one side of the film with a perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 1100, with a wet film thickness of 100 μm. After drying at 60° C. for 60 min until the liquid content drops below 5wt%, an ethanol-water mixture with a volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 min until the liquid content drops below 5wt%, a proton exchange membrane with a first perfluorosulfonic acid resin layer on one side is obtained;
[0113] S2: A perfluorosulfonic acid resin solution with a solid content of 10% and an EW value of 1100 is coated on the other side of the above-mentioned proton exchange membrane, and the wet film thickness is 100 μm. After drying at 60° C. for 60 minutes, the liquid content is reduced to less than 5wt%, and then an ethanol-water mixture with an alcohol-water volume ratio of 0.6:1 is sprayed on the surface, and after drying at 60° C. for 30 minutes, the liquid content is reduced to less than 5wt%, to obtain a proton exchange membrane with a second perfluorosulfonic acid resin layer on the other side;
[0114] S3 puts the above sample into a hot press at a temperature of 120° C. and a pressure of 2 MPa, and obtains a proton exchange membrane with a composite structure after hot pressing.
[0115] Test Example 1
[0116] Flatness test
[0117] Test sample: proton exchange membrane provided in Example 1-12;
[0118] Test method: Measure the membrane thickness at 12 different points on the corresponding sample proton exchange membrane, and calculate the average value and average deviation;
[0119] The specific test results are shown in Table 1:
[0120] Table 1
[0121] sample Average film thickness (μm) Mean value deviation (%) Example 1 18.4 4.7 Example 2 18.9 5.0 Example 3 18.6 4.8 Example 4 18.6 5.0 Example 5 9.5 4.6 Example 6 38.2 5.0 Example 7 18.5 4.9 Example 8 18.3 4.7 Example 9 18.3 5.1 Example 10 18.5 5.0 Embodiment 11 18.5 5.5 Example 12 18.3 6.1
[0122] It can be seen from the test data in Table 1 that the present invention adds a leveling process, that is, spraying an alcohol-water mixture on the surface after drying and then drying it again for leveling, so that the average value deviation can be reduced to below 5.0%, thereby significantly improving the flatness of the proton exchange membrane and helping to reduce the contact resistance between the proton membrane and the catalyst layer.
[0123] Test Example 2
[0124] Water retention test
[0125] Test samples: proton exchange membranes provided in Examples 1-12, and proton exchange membranes provided in Comparative Example 1;
[0126] Test method: Cut each of the above proton exchange membranes into samples of 5cm×5cm size, weigh them, and soak them in deionized water at a temperature of 23±2℃. Soak for 24 hours, take them out, absorb the surface moisture with absorbent paper, and weigh them again to calculate the water retention rate.
[0127] The specific test results are shown in Table 2:
[0128] Table 2
[0129]
[0130]
[0131] It can be seen from the test data in Table 2 that the present invention obtains proton exchange membranes with different water retention rates by coating perfluorosulfonic acid resin solutions with different EW values on both sides of the PTFE microporous layer, and the water retention rate of the obtained proton exchange membrane reaches more than 4.5%. It is explained that the proton exchange membrane obtained by this method can select a proton exchange membrane with a corresponding water retention rate according to the use conditions, effectively regulate the water management capacity of the membrane electrode, prepare proton exchange membranes with different water retention rate differences on both sides, enhance the back diffusion effect of water generated by the battery electrochemical reaction, provide more ion channels for the catalyst layer to enable it to have a rapid activation function, and maintain the water content in the proton exchange membrane and the catalyst layer during dry operation, effectively avoiding the high resistance problem under low humidity conditions.
[0132] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A proton exchange membrane, characterized in that: The proton exchange membrane comprises a first perfluorosulfonic acid resin layer, a microporous reinforcement layer and a second perfluorosulfonic acid resin layer stacked in sequence; Wherein, the EW value of the first perfluorosulfonic acid resin is 600-800, and the EW value of the second perfluorosulfonic acid resin is 900-1100.
2. The proton exchange membrane according to claim 1, characterized in that The thickness of the first perfluorosulfonic acid resin layer is 1-20 μm.
3. The proton exchange membrane according to claim 1, characterized in that The thickness of the second perfluorosulfonic acid resin layer is 1-20 μm.
4. The proton exchange membrane according to claim 1, characterized in that The microporous reinforcement layer is a porous polytetrafluoroethylene film layer; Preferably, the thickness of the porous polytetrafluoroethylene film layer is 3-100 μm; Preferably, the pore size of the porous polytetrafluoroethylene film layer is 0.05-1.0 μm; Preferably, the porosity of the porous polytetrafluoroethylene film layer is 40-90%.
5. A method for preparing a proton exchange membrane according to any one of claims 1 to 4, characterized in that: The preparation method comprises the following steps: After coating one side of the microporous reinforcement layer with a perfluorosulfonic acid resin solution with an EW value, first drying-leveling-second drying is performed in sequence; then coating the other side of the microporous reinforcement layer with a perfluorosulfonic acid resin solution with another EW value, first drying-leveling-second drying is performed in sequence; hot pressing is performed; and the proton exchange membrane is obtained.
6. The method for preparing a proton exchange membrane according to claim 5, characterized in that: The solid content of the perfluorosulfonic acid resin solution is 5-50%.
7. The method for preparing a proton exchange membrane according to claim 5 or 6, characterized in that: The temperatures of the first drying and the second drying are independently 50-70°C; Preferably, the first drying time is 10-120 min; Preferably, the first drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 wt %; Preferably, the second drying time is 10-120 min; Preferably, the second drying is performed until the liquid content of the perfluorosulfonic acid resin layer is below 5 wt %.
8. The method for preparing a proton exchange membrane according to any one of claims 5 to 7, characterized in that: The leveling method comprises the following steps: spraying a mixture of alcohol and water onto the surface of the perfluorosulfonic acid resin layer formed after the first drying; Preferably, the volume ratio of alcohol to water in the alcohol-water mixture is (0.5-1):1; Preferably, the alcohol in the alcohol-water mixture is selected from C1-C5 straight-chain or branched alkyl alcohol, preferably ethanol and / or n-propanol, and more preferably ethanol; Preferably, the spraying density is 1-10 μL / cm 2 .
9. The method for preparing a proton exchange membrane according to any one of claims 5 to 8, characterized in that: The temperature of the hot pressing is 80-200° C., and the pressure of the hot pressing is 1-10 MPa.
10. Use of the proton exchange membrane according to any one of claims 1 to 4 in the preparation of a fuel cell.
Citation Information
Patent Citations
Preparation method of compact and composite proton exchange membrane
CN102304234A